UPAYA SUKU REJANG DALAM MENJAGA BAHASA REJANG DIDESA TANJUNG KARET - Linda Astuti; Dyah Noor Intan; Prio Susanto; Imron Rosyadi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The purpose of this research are to describe and find how ethnic group REJANG efforts to preserve regional language,effort of parents and generations who lived in the Tanjung Karet village.This research uses qualitative method,data colectiontechniques were perfomed using primary dta through observation and interviews with research information while secondary data obtained from photo techniques.Which is obtained from multiple data sources through interviews with research information.Though the sosiolinguistik theory the resultsof this research show that people are still live at Tanjung Karet using rejng language for interactions in everyday activities such as when using a public speech the community still using rejang language though the event was attended by outsiders Tanjung Karet.The community using the rejang language for pray to god and other custom events.sentence allusion to the young people who use a foreign language with the local community.People still enthusiastically singings songs Rejang language when weddings.Parents using rejang language to their children from childhood.